New perspective of ceria nanodots for precise tumor therapy via oxidative stress pathway. Issue 8 (August 2022) - Wang, Hui; Wang, Qi; Dong, Jianyue; Jiang, Weiwei; Kong, Linghong; Zhang, Qiong; Liu, Hanping
Abstract: Ceria-based nanomaterials have aroused major attentions among the biomedical application research field in recent years. Most of the researches have mainly focused on promoting the functional healing therapies of normal cells/organs with cerium oxide compounds, while the applications of ceria-based materials employed on cancer curing processes have been merely mentioned. To explore the possible capabilities of cerium oxide nanomaterials exterminating tumor cells, innovatively, we synthesized the eco-friendly pure cerium oxide nanodots (CNDs), proving the prominent ability of CNDs used in tumor chemotherapy (CDT) via Fenton reaction with the highly presence of H2 O2 (acidic pH) in tumor tissues. CNDs reacted with the self-produced H2 O2 of tumor cells, which generated piled up toxic hydroxyl radical (·OH). The accumulated virulent ·OH restrained the growth of cancer cells intensively. This peroxidase-like activity, provided a distinguished paradigm for effective cancer curing treatment. We also verified the biosafety of CNDs applied on normal cells. Notably, not only did CNDs be harmless to normal cells, but also it protected them from the damages of reactive oxygen species (ROS). In normal cells/tissues, under the microenvironment of neutral pH and low level of H2 O2, the CNDs could effectively function as an annihilator inhibiting ROS. They reduced the damages caused by ROS, exhibiting catalase-like activity. The research we studied, which estimated CNDs thoroughly, has provided a new perspective to the future researches of the cerium oxide biomaterial applications. Abstract : Ceria nanodots (CNDs); Reactive oxygen species (ROS); Hydroxyl radicals (OH); Tumor recognition; Fenton reaction.